Benin : Technical Assistance Report-Public Investment Management Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
The Public Investment Management Assessment (PIMA) of Benin has brought to light an institutional framework of high quality but ineffective implementation. In accordance with the PIMA methodology applied in several countries, the mission focused on assessing the institutional strengths (such as the legal framework and organization) for each institution in the analytical framework, as well as its effective implementation. Benin was found to have a high-quality, relatively complete institutional framework. The country outperforms its peers in this regard, not only compared with the average for the countries of the subregion (the West African Economic and Monetary Union-WAEMU), but also the Sub-Saharan African countries that have already conducted a PIMA exercise (Figure 1). The effectiveness of the framework, however, is weak.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet